CAUSALITY RELATION BETWEEN ENVIRONMENTAL TAX REFORM AND DOUBLE DIVIDEND IN THE CZECH REPUBLIC - Muzzar Kresna (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2015)
Minimizing the impact of climate change and unsustainable practices of consumption-production could be achieved by environmental tax reform. Environmental tax reform applied by reducing the high tax burden on human labor and the business sector and raised taxes on pollution and the exhaustion on non-renewable natural resources. The aim of this study is to determine the direction of causality between environmental tax reform and economic indicator for sustainable development in the Czech Republic. Furthermore, this study attempts to analyze the interaction between environmental and fiscal policies that influence the prospects for a double dividend. Double dividend is condition where the environmental tax can produce two main benefits that are an environmental improvement and a decrease in the costs of the tax system. The result in this study shows that under relatively simple and neutral conditions, the double dividend in the case of Czech Republic does not arise. That condition indicates the environmental tax is narrower than the other tax it replaces.Keywords: Sustainable Development, Environmental Tax Reform, Double Dividend, Causality.